Classifying Sensors Depending on their IDs to Reduce Power Consumption in Wireless Sensor Networks - Brisha, Ayman Mohammd (International Journal of Online and Biomedical Engineering (iJOE), 2010)
Wireless sensor networks produce a large amount of data that needs to be processed, delivered, and assessed according to the application objectives. Cluster-based is an effective architecture for data-gathering in wireless sensor networks. Clustering provides an effective way for prolonging the lifetime of a wireless sensor network. Current clustering algorithms usually utilize two techniques, selecting cluster heads with more residual energy and rotating cluster heads periodically, in order to distribute the energy consumption among nodes in each cluster and extend the network lifetime. Clustering sensors are divided into groups, so that sensors will communicate information only to cluster heads and then the cluster heads will communicate the aggregated information to the processing center, and this may save energy. In this paper we show Two Relay Sensor Algorithm (TRSA), which divide wireless Sensor Network (WSN) into unequaled clusters, showing that it can effectively save power for maximizing the life time of the network. Simulation results show that the proposed unequal clustering mechanism (TRSA) balances the energy consumption among all sensor nodes and achieves an obvious improvement on the network lifetime.